2013
DOI: 10.1049/iet-pel.2012.0309
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐input DC/DC converter topology for hybrid energy system

Abstract: In this study, a multiple-input non-isolated DC/DC converter topology is presented. The proposed multiple-input DC/ DC converter is proficient for energy diversification from renewable and storage energy sources individually or simultaneously. It can be operated in buck, boost and buck-boost modes of operation with the capability of bidirectional power flow to achieve desired voltage level on either side. The development of small-signal modelling based on state-space averaging has been discussed. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 26 publications
4
123
0
Order By: Relevance
“…The MIBBC has advantages in most features while it is comparable in the remaining features with respect to number of ports. From Table 4 it is observed that the topology presented in [4] and the proposed work gives isolation without a transformer, but the total number of switches in [4] is more. This is the merit of the proposed work.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The MIBBC has advantages in most features while it is comparable in the remaining features with respect to number of ports. From Table 4 it is observed that the topology presented in [4] and the proposed work gives isolation without a transformer, but the total number of switches in [4] is more. This is the merit of the proposed work.…”
Section: Resultsmentioning
confidence: 96%
“…HESs can meet future energy demands; hence they are becoming increasingly popular in the area of electrical power systems. Multi-input converter (MIC) systems are becoming more common than multiple single-input DC-DC converters in many applications due to their advantages in terms of size, volume, flexibility in control, reliability, cost efficiency, and voltage regulation [1][2][3][4][5][6][7][8]. Different MIC topologies proposed by the research community mainly focus on nonisolated and isolated structures [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the comparison of the MBDC converter with other MICs has been carried out based on several parameters like total part counts in the converter, the efficiency and voltage stress of the converter and are illustrated in Table 4. A performance comparison of the MBDC converter has been carried out with three other converters proposed in the literature [6,13,24]. The output voltage of the converters due to the variation in duty ratios d1 and d2 is analyzed in a detailed manner, and the results are given in Figure 15.…”
Section: Resultsmentioning
confidence: 99%
“…Simple and compact structure, lower system complexity and reduced cost are the main attractive features of MICs. Compared to single-input converters, MICs can provide a reliable power supply, which is one of the potential merits of MICs [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The dc-dc converters manage power flow between the DC bus and battery. A number of bidirectional dcdc converters can be found in the literature [5][6][7][8][9][10][11][12][13][14]. The main focus in these converters is on achieving soft-switching in the power switches for a wide range of loading conditions to get rid of EMI and to enable very high frequency operation so that the size, and thus the cost, of the magnetics is minimized.…”
Section: Introductionmentioning
confidence: 99%